2007
DOI: 10.1073/pnas.0704329104
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 promotes endothelium-dependent vascular relaxation by activating endothelial nitric oxide synthase

Abstract: Reduced caloric intake decreases arterial blood pressure in healthy individuals and improves endothelium-dependent vasodilation in obese and overweight individuals. The SIRT1 protein deacetylase mediates many of the effects of calorie restriction (CR) on organismal lifespan and metabolic pathways. However, the role of SIRT1 in regulating endothelium-dependent vasomotor tone is not known. Here we show that SIRT1 promotes endotheliumdependent vasodilation by targeting endothelial nitric oxide synthase (eNOS) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
616
4
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 774 publications
(639 citation statements)
references
References 23 publications
17
616
4
2
Order By: Relevance
“…This point is of major importance because when eNOS-derived NO bioactivity is reduced, there is an impairment of endothelialdependent relaxation and endothelial dysfunction ensues (Mattagajasingh et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This point is of major importance because when eNOS-derived NO bioactivity is reduced, there is an impairment of endothelialdependent relaxation and endothelial dysfunction ensues (Mattagajasingh et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies point to Sirt1 as a chief regulator of NO synthesis in endothelium (Milne et al 2007;Pillarisetti 2008;Potente et al 2007) employing an Akt-mediated pathway of eNOS phosphorylation (Lovren et al 2009) or promoting eNOS catalytic activity through deacetylation of lysines 496 and 506 (Mattagajasingh et al 2007). As NO itself appears to reciprocally activate Sirt1 expression and activity (Ota et al 2007), then Sirt1-eNOS axis emerges as a decisive regulatory mechanism in CC endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In calorierestricted rats, it has been reported that SIRT1 promotes endothelialdependent vasodilation by targeting eNOS for deacetylation, thereby leading to enhanced nitric oxide production in the aorta. 32 Although Fukuhara's research demonstrated that resveratrol improved erectile function in STZ-induced diabetic rats by elevating the level of cyclic guanosine monophosphate, other pathophysiological factors underlying diabetes-induced ED, such as apoptosis and oxidative stress, were not reported. In this study, we demonstrated that resveratrol improved diabetes-induced ED by preventing oxidative stress and suppressing apoptosis.…”
Section: Resveratrol Restored Icp and Increased The Ratio Of Icp/mapmentioning
confidence: 99%
“…CR and resveratrol increase endothelial-derived nitric oxide (NO) (Csiszar et al, 2009;Nisoli et al, 2005), an important regulator of vascular relaxation and endothelial senescence (Oemar et al, 1998). Mattagajasingh et al (2007) showed that SIRT1 increases NO through deacetylation of eNOS. Further studies are required to determine whether CR-mediated beneficial functions in vascular senescence result from increased SIRT1.…”
Section: The Other Sirt Proteinsmentioning
confidence: 99%